PEMBENTUKAN KARAKTER ANAK MELALUI PERMAINAN TRADISIONAL GOAK MALING TALUH DI TK WERDHI KUMARA PUNGGUL BADUNG - Widya Kumala Ida Ayu Made; Sueca I Nyoman; Rai Parsua Gede (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Nowadays, traditional games have been abandoned by society. One of the causes is technology especially digital games has evolved rapidly. Traditional games have many benefits for children, it is: train them physically and mentally in creativity. It is a part of character building that can be started at an early stage. And some problems will be discussed, they are: (1) How is the form of the traditional game Goak Maling Taluh used to establish the children's character at TK Werdhi Kumara Punggul Badung? (2) What assessments of character education are taught through the traditional game Goak Maling Taluh at TK Werdhi Kumara Punggul Badung? (3) How is the implication of the traditional game Goak Maling Taluh against character building at TK Werdhi Kumara Punggul Badung? This research aims to examine the form, the assessment, and the implication of the traditional game Goak Maling Taluh used to build children's character at TK Werdhi Kumara Punggul Badung The theory used to analyze the problems is a structural-functional theory by Malinowski, character theory by Lickona, behavioristic theory by Gagne. The subject of this research is the children at TK Werdhi Kumara Punggul Badung. The method of collecting data is non-participant observation, semi-structured interview, literature and documentation. The data that has been collected is analyzed by qualitative descriptive method with the steps of data reduction, data presentation, conclusion/ verification. The research result shows (1) The form of traditional game Goak maling Taluh used to build children's characters at TK Werdhi Kumara Punggul Badung is classified into three stages, they are planning stage, implementation stage, and evaluation stage, (2) What assessments of character education taught through traditional game Goak maling Taluh at TK Werdhi Kumara Punggul Badung, they are: religious assessment, honest assessment, tolerance assessment, hard-work assessment, discipline assessment, (3) The implications of traditional game Goak Maling Taluh against children's character building at TK Werdhi Kumara Punggul Badung, they are implication against physics, implication against attitude, implication against the knowledge